An Overview of Current Trends in European AOSE Research (Informatica, 2025)
The agent oriented approach is doing great steps towards its (not yet reached) maturity; from a software engineering point of view, it is today positively used for the analysis and design of complex systems. In this paper, which is related to the activity of the AgentLink AOSE TFG (Agent Oriented Software Engineering Technical Forum Group), we provide a perspective of current research trends in this area with a specific attention for results coming from European groups. We start with a discussion of what are agents, specially from the perspective of the software engineer. We present recent trends in modelling agents and multi-agent systems, and then we review the different activities in the agent development process: from analysis and design to implementation, verification and finally testing.